Local government reform beyond privatization and amalgamation: advances in the analysis of inter-municipal cooperation - Bel, G; Elston, T; Esteve, M; Petersen, OH (Routledge, 2024)
Inter-municipal cooperation, where two or more local governments jointly provide one or more public services across their jurisdictions, is an increasingly prevalent mode of public administration. In part, this reflects the limited success of prior rounds of privatization and amalgamation reform – and the continuing desire to economize and improve regional coordination. In part, it speaks of the wider policy fashion for seeking collaborative solutions to public problems. This article introduces a special issue on “the drivers and effects of inter-municipal cooperation.” It reviews the current evidence base and the contributions of six papers, and suggests productive avenues for future research.